Experience of nurses in caring for patients with dementia - Lapinskienė, Lukrecija; Kevišienė, Vlastimila (Slauga. Mokslas ir praktika, 2023)
The research reveals the positive and negative experiences of nurses in working with persons with dementia, allows to analyze the emerging problems and difficulties and to properly solve them in practical work, thereby improving the quality of healthcare services. The purpose of the study is to analyze the experience of nurses in caring for patients with dementia. Research methods. The applied qualitative research method of descriptive phenomenology reveals and explains the researched phenomenon as it is understood and experienced personally by each individual. The study interviewed 6 nurses working in the X nursing home. Research results and conclusions. The study revealed that dementia requires individual care and nursing. When working with patients with dementia, nurses have positive and negative experiences, and the involvement of relatives in patient care has a positive effect on both the physical and emotional state of the patient. Dementia requires individualized care and nursing as well as support and fulfillment of basic needs.